2019
DOI: 10.1051/0004-6361/201936049
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the exoplanet mass-radius relation

Abstract: Context. Mass and radius are two fundamental properties for characterising exoplanets, but only for a relatively small fraction of exoplanets are they both available. Mass is often derived from radial velocity measurements, while the radius is almost always measured using the transit method. For a large number of exoplanets, either the radius or the mass is unknown, while the host star has been characterised. Several mass-radius relations that are dependent on the planet's type have been published that often a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Before fitting for the planet's albedo, we first used the posterior mass estimate from the orbit fit and radial velocity semi-amplitude, and then inferred the planet's radius from an empirical mass-radius relationship along with the approximate equilibrium temperature of planet d. 19 A simple least-squares optimization finds the albedo that minimizes the distance between the 4 epochs of photometry and the Lambertian phase curve associated with the orbit posteriors. The result, in Figure 6, illustrates the four photometric data points, the best-fit flux curve, and the flux curve of the true planet parameters.…”
Section: Photometry and Phase Curve Analysismentioning
confidence: 99%
“…Before fitting for the planet's albedo, we first used the posterior mass estimate from the orbit fit and radial velocity semi-amplitude, and then inferred the planet's radius from an empirical mass-radius relationship along with the approximate equilibrium temperature of planet d. 19 A simple least-squares optimization finds the albedo that minimizes the distance between the 4 epochs of photometry and the Lambertian phase curve associated with the orbit posteriors. The result, in Figure 6, illustrates the four photometric data points, the best-fit flux curve, and the flux curve of the true planet parameters.…”
Section: Photometry and Phase Curve Analysismentioning
confidence: 99%
“…We then compared the available measurements of mass and radius contained in Exo-MerCat with the verification sample used in Ulmer-Moll et al (2019), as shown in Figure 6.…”
Section: Performancementioning
confidence: 99%
“…Unsurprisingly, the theoretical relation appears to be in agreement with both the data belonging to Exo-MerCat, as well as the validation sample. The sample produced by Exo-MerCat, however, contains more elements, with a few candidates covering regions in the mass-radius parameter space which are not included in the verification sample used by Ulmer-Moll et al (2019). It could be therefore possible that, when repeating similar analyses, small differences in the theoretical relations would appear.…”
Section: Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Using the sample of known transiting planets, several studies have been conducted to investigate the mass-radius relation for exoplanets, taking into account the role of the flux received from the star (Enoch et al 2012;Kane & Gelino 2012;Weiss et al 2013;Chen & Kipping 2017;Bashi et al 2017;Ulmer-Moll et al 2019) and also their bulk composition (Swift et al 2012;Dorn et al 2015Dorn et al , 2017. These studies about the formation and evolution of exoplanetary systems have shown that planet radii increase with the mass in the case of low-mass planets, while these two quantities present a constant or even negative relation for high-mass planets (higher than 100 M ⊕ ).…”
Section: Introductionmentioning
confidence: 99%